Blind hole drilling of hybrid aluminium-rice husk ash (ARHA) composite using rotary electro-discharge drilling. (2018) - Choudhary, Rajesh; Singh, Gagandeep; Singh, Sahibpreet; Dhanjal, Shubham; Singh, Prem; Kathuria, Sandeep; Singh, Varinder
Abstract: This study deals with the Material Removal Rate(MRR) of Aluminium-Rice Husk Ash composite and Tool Wear Rate of copper electrode used as drilling tool. The composite was prepared with 9% wt. of RHA and Mg in equal proportions per total wt. of Aluminium used, using Stir casting method. RHA which is difficult to decompose in nature is used to reduce the agricultural waste. It is found that hybrid MMC (HMMC) based on ARHA is lightweight material and useful in automobile and aerospace industries. Addition of RHA in Aluminium increases tensile strength, compressive strength and hardness but decreases ductility. This paper presents effect of process parameters on the response parameters; MRR of ARHA and TWR of copper electrode. It was observed that the gap current was the dominating parameter for MRR and TWR followed by pulse-on time, tool polarity, duty cycle and gap voltage. Negative tool polarity of copper tool results more MRR and TWR than positive tool polarity. Negative tool polarity is good in case of higher MRR compromising on the surface finish end where as positive tool polarity is good in case of lesser TWR.